Public Relations Management in Senior High School Negeri 2 Tambang - Rini Setyaningsih; Cici Cahya Kemang; Arrum Intan Sari (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
Abstract: This study aims to determine how public relations management is at State Senior High School 2 Tambang. This type of research uses qualitative analysis. Data collection techniques are obtained through participant observation, in-depth individual interviews and documentation studies. Researchers conduct data analysis by reducing previously obtained data, then presenting the data and drawing conclusions. This study found that 1) Public relations communication is carried out by a team both online and offline for schools, 2) Public Relations of State Senior High School 2 Tambang has an ethical organizational culture in order to create a conducive learning atmosphere, 3) public opinion in public relations of State Senior High School 2 Tambang in the form of news is packaged attractively and easily understood, conducting two-way traffic communication, 4) basic public relations techniques by conveying messages or information in writing or verbally, 5) public relations publication media used by State Senior High School 2 Tambang using email, social media or directly to the school's public relations, 6) building a public image, 7) marketing educational services, 8) building partnerships with stakeholders, 9) electronic public relations E-PR, 10) school public relations programs Keywords : Management, Public Relations, School